Clinical and prognostic role of interim 18F-FDG PET/CT in elderly Hodgkin lymphoma: a dual-center experience. Issue 13 (9th November 2020) - Albano, Domenico; Mazzoletti, Angelica; Zilioli, Vittorio Ruggero; Muzi, Cristina; Crucitti, Lara; Tucci, Alessandra; Pagani, Chiara; Re, Alessandro; Rossetti, Claudio; Giubbini, Raffaele; Bertagna, Francesco
Abstract: Hodgkin lymphoma (HL) has a bimodal age distribution curve, with a second peak in people aged more than 60 years. Interim PET/CT (iPET/CT) is highly predictive for PFS and OS in young HL, but it has not been sufficiently studied in the elderly. In this retrospective dual-center study, 82 patients with HL and aged 65 or more who performed iPET/CT were included. At iPET/CT, 60 patients had a complete metabolic response, 18 partial responses, and 4 progressions of disease. Baseline PET/CT metabolic features were not significantly correlated with the metabolic response at interim. In patients with interim complete metabolic response, PFS and OS were significantly longer than in patients without complete response( p < 0.001 and p = 0.004). Patients with negative iPET had 2-year PFS and OS rates of 57 and 88% compared with 24 and 58% in patients with positive iPET ( p < 0.001). iPET/CT results demonstrated to be independent prognostic factors for PFS and OS.